Optimalisasi Produksi dan Pemasaran Maggot sebagai Pakan Ternak Alternatif: Program Pemberdayaan UMKM di TPS3R Ngudi Lestari - Nofika Febriyanti; Nuzulia Ulfiyatun Ni’mah; Agil Tyas Bagus Saputra; Iqbal Andrea Salasah; Farikha Kamilatul Azizah; Erika Cahya Aprilia; Muhammad Syifa’ Renaldy Umar; Kauna Sahilah; Puji Lestari (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The need for efficient, economical, and environmentally friendly animal feed in Indonesia, especially for small and medium-scale farmers, requires innovative solutions. This community service program aims to optimize the production and marketing of maggot as an alternative animal feed through the empowerment of MSMEs at TPS3R Ngudi Lestari. A participatory approach was implemented through two main stages: maggot production training and a digital marketing workshop. The results showed a significant increase in both the production capacity and quality of maggot, as well as an improvement in digital marketing skills among MSMEs. The training enhanced participants' technical abilities in substrate management, production efficiency, and post-harvest processing, leading to higher and more consistent production outcomes. Meanwhile, the digital marketing workshop equipped MSMEs with strategies to expand market reach through online platforms, branding, and content creation. Despite challenges such as substrate variability and digital infrastructure limitations, innovative solutions like substrate diversification and improved environmental monitoring were successfully applied. This program not only boosted the local economy but also contributed to a more sustainable livestock sector by integrating circular economy principles. In conclusion, the program demonstrates the potential of combining maggot production with digital marketing strategies to create a sustainable business model for MSMEs, serving as a replicable example for community empowerment within the context of a circular economy and sustainable agriculture in Indonesia